Patterns of abuse of elderly people in Brazil: analysis of notifications - Fabiana Martins Dias de Andrade; Ísis Eloah Machado; Maria Imaculada de Fátima Freitas; Maria de Fatima Marinho de Souza; Deborah Carvalho Malta (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
This study aimed to describe the characteristics of elderly people abuse notifications by gender and to assess notification patterns according to gender. We analyzed data from the Brazilian Information System for Notificable Diseases (SINAN) in 2017. We carried out a descriptive analysis of victim characteristics, violence, and the probable perpetrator according to gender. Pearson's χ2 test was used to assess the significance between groups. Then, we verified the main relationships between the studied characteristics and the victim's gender by simple correspondence analysis (SCA). Thus, 17,311 cases/suspicions of elderly people abuse were notified, corresponding to 7.2% of the total number of violence notifications. Of these victims, 50.4% were white, 42.3% were married, and 17.2% had a disability/disorder; 76.9% occurred at home, 62.8% included physical violence, and 49.5% were cases of repeated violence. Most perpetrators were men (62%), and violence by two or more perpetrators was observed in 62.8% of the cases. SCA evidenced inequalities in older adults' gender, which proved to be higher among women. Physical violence was the most common among younger and old individuals, whereas neglect/abandonment tended to occur more frequently among the oldest individuals, and was most often committed by daughters. In sum, this study demonstrated evidence of gender-based violence, especially among older adults. Disability proved to be an essential characteristic for neglect/abandonment in older adults. In this context, policies are needed to reduce gender inequalities and implement a care network for older adults who are victims of violence.